From Multivalent Writing to a Poetics of the Book: A Media-Specific Analysis of Mary Ruefle’s A Little White Shadow - Catherine Ann Winters (Sillages Critiques)
Mary Ruefle’s A Little White Shadow (2006) asks the reader to consider the book as more than a container for poetry by playing with our expectations of print books: namely stability, permanence, and authority. This work of erasure reproduces the marks Ruefle made to obscure words in the source text of the same name by Emily Malbone Morgan, published in 1889, by creating a facsimile of the original altered with white correction fluid. By utilizing the material object as an essential element of the poem, Ruefle engages this form to move beyond the concept of the book as object or apparatus for presenting poetry. She achieves this by physically erasing an already historically “erased” book – a text that was largely unavailable and unremembered at the time Ruefle published her poem – that treats themes of writing, reading, and literature. This aligns with Johanna Drucker’s definition of the artist’s book as a fine arts practice that interrogates the form and meaning of the medium and questions what a book is. Through this same relationship of form and content, Ruefle develops a poetics of the book. Ultimately, she rejects the idea that the poetry book is dead with the caveat that the codex as a de facto form that does not affect the meaning of the poetry is dying. Instead, Ruefle weaves our expectations and assumptions about the medium into her erasure poem to make this formerly default form an active part of her project.